2014
DOI: 10.4155/fmc.14.134
|View full text |Cite
|
Sign up to set email alerts
|

Library Construction, Selection and Modification Strategies to Generate Therapeutic Peptide-Based Modulators of Protein–Protein Interactions

Abstract: In the modern age of proteomics, vast numbers of protein-protein interactions (PPIs) are being identified as causative agents in pathogenesis, and are thus attractive therapeutic targets for intervention. Although traditionally regarded unfavorably as druggable agents relative to small molecules, peptides in recent years have gained considerable attention. Their previous dismissal had been largely due to the susceptibility of unmodified peptides to the barriers and pressures exerted by the circulation, immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 166 publications
0
8
0
Order By: Relevance
“…[7] Particularly for longer peptides, an element of rational design can help focus the search on sequences likely to enhance function. In some design problems it is important to consider binding specificity and to improve the affinity of a peptide for one target but not for paralogous family members; this is a consideration in many of the case studies described below.…”
Section: Methods For Improving Native Peptide Sequence and Scaffold Smentioning
confidence: 99%
“…[7] Particularly for longer peptides, an element of rational design can help focus the search on sequences likely to enhance function. In some design problems it is important to consider binding specificity and to improve the affinity of a peptide for one target but not for paralogous family members; this is a consideration in many of the case studies described below.…”
Section: Methods For Improving Native Peptide Sequence and Scaffold Smentioning
confidence: 99%
“…Generally, the imaging component of probes includes iron-or Gd-based contrast agents, while the targeting ligands popularly studied are antibodies, peptides and aptamers. Peptides are particularly advantageous because of their low molecular weight, ease of transportation and storage, great stability and ease of modification 17,18 . For example, recent studies have demonstrated that the use of  v  3 integrin, aminopeptidase N, and angiopoietin could provide targeting of a tumour and its vascular endothelial cells 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Many rational design approaches, library screens, and selection systems exist and have resulted in the successful identification of molecules capable of binding to given TF targets, but a key challenge remains in ensuring that target binding will translate into ablation of function. 17 , 19 Selection using a well-studied target exemplar in this work was required to provide suitable antagonists that validate the assay concept. Various methodologies have produced peptide-based cJun antagonists that target the broad LZ binding interface.…”
Section: Introductionmentioning
confidence: 99%